IAIMS Architecture - Hripcsak, George (American Medical Informatics Association, 1997)
An information system architecture defines the components of a system and the interfaces among the components. A good architecture is essential for creating an Integrated Advanced Information Management System (IAIMS) that works as an integrated whole yet is flexible enough to accommodate many users and roles, multiple applications, changing vendors, evolving user needs, and advancing technology. Modularity and layering promote flexibility by reducing the complexity of a system and by restricting the ways in which components may interact. Enterprise-wide mediation promotes integration by providing message routing, support for standards, dictionary-based code translation, a centralized conceptual data schema, business rule implementation, and consistent access to databases. Several IAIMS sites have adopted a client-server architecture, and some have adopted a three-tiered approach, separating user interface functions, application logic, and repositories.